Determination of the Cytotoxic Effect of Different Leaf Extracts from Parinari curatellifolia (Chrysobalanaceae) - Kundishora, Anesu (J Toxicol, 2020)
Despite plants being a rich source of useful chemical compounds with different pharmacological properties, some of these compounds may be toxic to humans. Parinari curatellifolia, among its other important pharmacological activities, has been shown to have significant antiproliferative activity on cancer cell lines. Toxicity studies are required to determine the safety profile of P. curatellifolia in the consideration of its potential pharmaceutical benefits as a source of lead compounds in cancer therapy. The effects of P. curatellifolia on both the integrity of the erythrocyte membrane and on normal cells were determined. The dried leaf powder of P. curatellifolia was used in serial exhaustive extraction procedures using hexane, dichloromethane, ethyl acetate, acetone, ethanol, methanol, and water as solvents in addition to extraction using DCM: methanol in equal ratio. Alkaloids, flavonoids, and saponins were isolated from the ethanol extract. The leaf extracts were tested for haemolytic activity on sheep erythrocytes at concentrations of 0.625 to 5 mg/ml. The extracts were also tested for toxicity activity on normal mammalian cells such as the BALB/c mice peritoneal cells using the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) at the concentrations of 6.3 to 50 μg/ml. In the haemolysis assays, none of the plant extracts had a significant haemolytic activity with the saponin-enriched extract having the maximum haemolytic activity of 12.2% for a concentration of 5 mg/ml. In the MTT cell viability assay, none of the 11 plant extracts had significant cytotoxicity. The water extract, however, had significant (p < 0.01) proliferative activity towards the murine immune cells at all concentrations. P. curatellifolia leaf extracts were, therefore, not toxic to both erythrocytes and immune cells, and the water extract may have immunostimulatory effects. It is concluded that P. curatellifolia leaf extracts are not toxic in vitro and, therefore, our results support the use of the plant for ethnomedicinal use.